2012
DOI: 10.1142/s1088424612500514
|View full text |Cite
|
Sign up to set email alerts
|

The overhanging carboxylic acid strategy: an alternative route to the porphyrin core expansion/modification for the coordination of large metal ions

Abstract: This account summarizes how the binding properties of a regular porphyrin macrocycle for large cations can be significantly modified and even tuned when the surrounding skeleton delivers at least one carboxylic acid group close to the N -core. While kinetics of metal insertion are drastically improved, unique dinuclear species can be obtained with a possible control of the nuclearity. The first incorporation of an α-core emitter radioisotope of particular interest for cancer therapy was recently demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…By doing so, several combinations of homo and heterobimetallic species would be virtually accessible, thus defining a dynamic library of metalloporphyrins. This strategy lies on recent results from our group obtained with bis-strap overhanging carboxylic acid(s) porphyrins. , We have indeed shown that two types of bimetallic complexes were accessible with such ditopic chelates (Figure ). On the one hand, “bridged” C 2 -symmetric homobimetallic species with the metal ions on opposite sides both bound to the porphyrin N-core and to a carboxylate of a strap (type I, lower part in Figure ) were observed with the C 2 -symmetric chelate 1 and Hg­(II), Cd­(II), Pb­(II), and Bi­(III) ions [ 1Hg 2 , 1Cd 2 , 1Pb 2 , and 1­(BiOAc) 2 ] .…”
Section: Introductionmentioning
confidence: 96%
“…By doing so, several combinations of homo and heterobimetallic species would be virtually accessible, thus defining a dynamic library of metalloporphyrins. This strategy lies on recent results from our group obtained with bis-strap overhanging carboxylic acid(s) porphyrins. , We have indeed shown that two types of bimetallic complexes were accessible with such ditopic chelates (Figure ). On the one hand, “bridged” C 2 -symmetric homobimetallic species with the metal ions on opposite sides both bound to the porphyrin N-core and to a carboxylate of a strap (type I, lower part in Figure ) were observed with the C 2 -symmetric chelate 1 and Hg­(II), Cd­(II), Pb­(II), and Bi­(III) ions [ 1Hg 2 , 1Cd 2 , 1Pb 2 , and 1­(BiOAc) 2 ] .…”
Section: Introductionmentioning
confidence: 96%
“…In all of the above-mentioned examples, however, there was no specific design of the macrocycle, resulting in a lack of versatility. Conversely, appending a binding motif such as a carboxylic acid in the vicinity of the primary coordination site has proved to be a versatile strategy for the formation of bimetallic species with the period 6 main-group and late transition metals . Such an environment allows the stabilization of unique homodinuclear complexes with Pb(II) (e.g., 2Pb 2 in Figure a) and Hg(II) cations, in which each metal ion is bound to both the N core and a hanging carboxylate group.…”
Section: Introductionmentioning
confidence: 99%
“… The substitution of the anisole moieties for phenol and quinone units strongly affects the kinetics of Zn II complexation in the following order: L Ome ≪ L OH < L Q (hours vs. minutes or less). Two factors can be invoked to explain this phenomenon: the decrease of steric crowding around the site of complexation (calixarene small rim) and the possible participation of the O ‐lone pairs as transient donors favoring approach and desolvation of the Zn II cation [54] . Indeed, these O ‐lone pairs differ strongly by their donor ability and orientation.…”
Section: Resultsmentioning
confidence: 99%